Learning Rails 5 Rails from the outside in - Locklear, J. Mark; Bulpett, Barnabas; Gruber, Eric J. 1976- (O'Reilly, 2016)
"If you're a web developer or designer ready to learn Ruby on Rails, this hands-on guide is the ideal way to get started. Rather than toss you into the middle of the framework's Model-View-Controller architecture, as many books do, Learning Rails 5 begins with the foundations of the Web you already know. You'll learn how to create something visible with Rails' view layer before diving into the more difficult inner layers: the database models and controller code. All you need to begin your Rails journey is HTML experience. Each chapter includes exercises and review questions to test your understanding as you go"--Back cover.
Includes index. - Online resource; title from PDF title page (EBSCO, viewed September 6, 2016)
Keywords: Ruby on rails (Electronic resource); Ruby (Computer program language); Web site development; Application software -- Development; Ruby (Langage de programmation); Sites Web; Développement; Logiciels d'application; Développement; COMPUTERS; Programming; Object Oriented; Application software; Development; Websites; Ruby (programmeertaal)